Widening the lens to childhood: relevance and lifetime risk of kidney failure. Issue 3 (May 2019) - Rampersad, Christie; Dart, Allison
Abstract : Purpose of review: Lifetime risk of outcomes is emerging as a highly relevant health indicator, even in the context of low absolute risk of disease progression in short time frames. Evidence to support this concept for kidney failure is increasing, with growing emphasis on the long-term impact of risk factors occurring early in life . Recent findings: Proteinuria and stage of chronic kidney disease (CKD) are now established predictors of CKD progression in children, and youth with type 2 diabetes are emerging as a group at significant risk. Recent population-based studies have also examined the lifetime risk of end-stage renal disease in individuals with any childhood CKD. A recent study found that even in the absence of biomarkers of renal injury, childhood CKD can increase the lifetime risk of end-stage renal disease four-fold, and up to 10-fold in adults less than 40 years of age. Summary: Children with CKD are at high lifetime risk of kidney failure and require follow-up. Identifying children at highest lifetime risk through the use of biomarkers and risk equations, and determining the optimal duration and intensity of follow-up requires further research.